‘Experts’, settlers and Africans: The production of local agricultural and veterinary knowledge in Southern Rhodesia (1897–1914) - Gargallo, E. (Journal of Imperial and Commonwealth History, 2022)
Historiography dealing with the development of colonial science in Africa and the production of ‘local knowledge’ has gradually become more complex and nuanced. Interactions as well as conflicts between local and imperial knowledge are highlighted, together with the partial incorporation of African knowledge into scientists’ ideas, and the contradictions within scientific institutions. The aim of this paper is to analyse how agricultural and veterinary scientific discourses and policies were constructed in Southern Rhodesia (present day Zimbabwe) before the First World War, which ideas and practices became accepted as scientifically sound, and who was expected to master this expertise. Evidence shows how the links and collaboration between international, imperial, and Rhodesian institutions and individuals were far from unproblematic; how the relationship between scientists and the growing number of European farmers was often conflictive; and how scientists’ views of African knowledge and practices were ambiguous and contradictory. In line with other British colonies, Rhodesian agricultural and veterinary science and policies went through a process of gradual ‘localisation’ in this period. Rhodesia, however, presented some peculiarities: due to its short history and small European population, it was more a ‘Southern African’ localisation rather than Rhodesian. Collaboration and knowledge exchange between white settlers and officials were very limited. And, even if officials’ views and interventions were not uniformly negative and oppressive towards Africans, the incorporation of African practices and knowledge into colonial science were still far away.